Front Cover: Enhanced Spin Hall Effect in S‐Implanted Pt (Adv. Quantum Technol. 1/2021). Issue 1 (15th January 2021) - Shashank, Utkarsh; Medwal, Rohit; Shibata, Taiga; Nongjai, Razia; Vas, Joseph Vimal; Duchamp, Martial; Asokan, Kandasami; Rawat, Rajdeep Singh; Asada, Hironori; Gupta, Surbhi; Fukuma, Yasuhiro
Abstract : The spin Hall effect is a spin–orbit‐coupling‐related phenomenon, in which the charge current generates a transverse spin current and vice versa. Platinum is a well explored spin Hall material due to large spin–orbit coupling and high conductivity, but its interconversion efficiency is of around 10% only. In article number 2000112, Surbhi Gupta, Yasuhiro Fukuma, and co‐workers employ the pioneering technology of ion implantation to develop a new spin Hall material, sulfur‐implanted platinum Pt(S), demonstrating an interconversion efficiency of 50%. The designed Pt(S) achieves high spin Hall conductivity, which determines its suitability for next‐generation spin–orbit‐torque‐driven logic and memory device applications.